Graphene oxide gold nanostructure based surface enhanced raman scattering DNA biosensor for the detection of meat species / Md. Ibrahim Khalil - Md. Ibrahim , Khalil (2020)
Authentication, detection and quantification of the ingredients, and adulterant in the food, meat and meat products are of high importance in current days. However, the conventional meat species detection techniques based on lipid, protein and DNA biomarkers have been confronting challenges due to the poor selectivity, sensitivity, and unsuitability for processed food products or complex food matrices. Hence, nanoparticle based DNA biosensing strategies have attracted the most interests and considered as one of the best alternatives to conventional strategies. Among these, surface enhanced Raman scattering (SERS) has gained the substantial acceptance as an excellent, fast and ultrasensitive sensing technique due to its ability to produce molecule specific distinct spectra, narrow spectral bandwidth and multiplexing ability. However, the performance of the SERS DNA biosensor relies on the DNA probe length, platform composition, presence and position of Raman tags and the chosen sensing strategy. Herein, it was demonstrated for the first time SERS DNA sensing for the detection meat species using short-length DNA probe and two different strategies of Raman tag attachment either co adsorbed with or intercalated in the DNA probe sequences. Moreover, SERS-active dual platforms comprising of graphene oxide-gold nanoparticles (GO-AuNPs), graphene oxide-gold nanorod (GO-AuNR), and AuNPs were used in different combinations. At the first sensing strategy, GO-AuNP functionalized with capture probe 1 (CP1) and AuNPs with co-adsorbed CP2 and Cy3 were used to fabricate the SERS biosensor for the quantitative detection of the Malayan Box Turtle (MBT). Hybridization mediated coupling of the two platforms generated the huge amplified SERS signal which in consequence facilitated to achieve a greater sensitivity with a limit of detection (LOD) of 10 fM (synthetic target DNA) and 100 fM (real sample). In the second strategy, a uniquely designed Raman tag (ATTO Rho6G) integrated signal probe (SP) sequence immobilized AuNPs and the CP DNA functionalized GO-AuNR were utilized to detect the pig species. This biosensing approach showed an outstanding sensitivity with an LOD of 100 aM as well as validated with DNA extracted from pork sample (LOD – 1fM). Finally, a duplex SERS DNA biosensor was fabricated following the same strategy using Cy3 and ATTO Rho6G intercalated SP sequences specific to MBT and pig species respectively as well as GO-AuNPs and AuNPs as sensor platforms for the simultaneous detection of both species. In the presence of the target DNA sequences, covalent linking of the CP functionalized GO-AuNPs and SP functionalized AuNPs triggered the huge SERS signal enhancement due to the multi-component agglomeration. The duplex DNA biosensor exhibited an excellent sensitivity with an LOD of 10 fM for the synthesized target DNA and 100 fM for real sample. Moreover, the fabricated SERS biosensors showed an outstanding selectivity and specificity to differentiate the DNA sequences of the closely related non-target species and the target DNA sequences with single and three nucleotide base-mismatches. The developed short-length DNA conjugated dual platforms based SERS biosensors proved as a selective, sensitive and convenient technology for the detection of single and dual species, hence could be universally applicable for the versatile applications and opted for the simultaneous multiplex detection.